2015
DOI: 10.4103/0972-0707.168811
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salivary contamination on the dentin bond strength of two different seventh generation adhesive systems: In vitro study

Abstract: Aim:To investigate the effect of salivary contamination on the bond strength of two different seventh generation adhesive systems.Materials and Methods:Sixty caries-free human premolars with flat dentin surfaces were randomly divided into six groups of 10 teeth each and bonding was done using seventh-generation bonding agents Adper Easy One (3M ESPE) and Xeno V (Dentsply). Following the bonding procedure, resin composite was bonded to the surfaces using a plastic mould. The prepared specimen with composite cyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…In stage 1 contamination, the saliva present on the prepared surface could have acted as a buffer and reduced the etching capacity of monomers in the U adhesive whose pH is acidic (pH = 2) and resulted in reduced penetration into the dentinal tubules and resulting in a decreased bond quality. This observation conforms to the earlier studies [ 21 , 22 , 24 , 45 , 46 ], which established that the salivary contamination in universal adhesives could be detrimental. The influence of salivary contamination in stage 3 may be justified as the adsorption of glycoproteins onto the polymerized adhesive surface, which results in oxygen inhibition and reduced bonding capacity [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In stage 1 contamination, the saliva present on the prepared surface could have acted as a buffer and reduced the etching capacity of monomers in the U adhesive whose pH is acidic (pH = 2) and resulted in reduced penetration into the dentinal tubules and resulting in a decreased bond quality. This observation conforms to the earlier studies [ 21 , 22 , 24 , 45 , 46 ], which established that the salivary contamination in universal adhesives could be detrimental. The influence of salivary contamination in stage 3 may be justified as the adsorption of glycoproteins onto the polymerized adhesive surface, which results in oxygen inhibition and reduced bonding capacity [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…The universal adhesive can be used either in etch-and-rinse or self-etching mode, and the previous studies on the salivary contamination have conveyed that saliva contaminations can be deleterious. One study [ 21 ] observed that contamination significantly reduced the bond strength and another study [ 22 ] stated that the reduction was more pronounced when the contamination occurred before light curing than after. In both the studies, decontamination involving reapplication of the adhesive restored the bond strength.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Bhatia et al in their study found that reapplication of the bonding agent yielded better bond strength. 17 …”
Section: Discussionmentioning
confidence: 99%